The protective role of psychological resilience in the recovery of children’s athletic sports injuries: a mechanistic study based on emotion regulation and self-efficacy - Zhang, Benke; Li, Chunming; Shi, Menghui; Li, Shenguang; Lv, Jiyong (Frontiers in Psychology, 2026)
PurposeThis study explored the protective role of psychological resilience in children’s sports injury recovery, and verified the chain mediating effect of emotion regulation (cognitive reappraisal, expressive suppression) and sports self-efficacy, to provide empirical evidence for psychological intervention in children’s injury rehabilitation.MethodsA total of 128 injured children aged 8–12 years were selected via cluster sampling from the school (March 2024–March 2025). A 6-month follow-up (T0: baseline, T1: 3 months, T2: 6 months) was performed with scales measuring psychological resilience, emotion regulation (child version), sports self-efficacy, and injury recovery progress. SPSS 26.0 was used for descriptive and correlation analyses, and Mplus 8.3 for longitudinal mediation and chain mediation models.ResultsThis study uses longitudinal mediation analysis to explore associative pathways, acknowledging unmeasured confounders may influence results. Baseline resilience was positively correlated with T1/T2 recovery (r = 0.407, 0.462; both p < 0.001). β = 0.196 is consistently reported for T0 resilience → T1 self-efficacy, but negatively predicted T1 expressive suppression (β = −0.179, p < 0.05); T1 self-efficacy was positively associated with T2 recovery (β = 0.372, p < 0.001). Key limitations include single-time-point measurements of resilience (T0 only) and self-efficacy (T1 only), which restrict causal inference. Two chain paths were significant: “resilience → cognitive reappraisal → self-efficacy → recovery” (indirect effect = 0.098, 95% CI = [0.065, 0.131]) and “resilience → expressive suppression → self-efficacy → recovery” (indirect effect = −0.029, 95% CI = [−0.048, −0.012]), with total mediation accounting for 37.9% of total effect. This study uses longitudinal mediation analysis to explore associations, acknowledging unmeasured confounders may influence results.ConclusionResilience affects recovery via two chains: improving cognitive reappraisal to enhance self-efficacy, and reducing expressive suppression to boost self-efficacy. Cognitive reappraisal is a more positive mediating path and a core target for psychological intervention.